Impact of physiological amount of E. coli on the efficiency of stallion semen cryopreservation - Ткачов, О. В.; Шеремета, В. І. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
The biological effect of the absolute number of colony forming units of coliform bacteria and the total number of saprophytic bacteria in the semen of the sires of Ukrainian selection on its physiological parameters before and after cryopreservation has been studied for the first time. It has been found out for the first time that the correlation coefficient of the number of coliform bacteria in the native semen with the thawed semen mobility is –0,54 (p<0.01), with the semen survival at 37°C –0,54 (p<0,01). The total number of saprophytic bacteria in the semen had significantly less impact on the biological indicators of the thawed semen than E. coli and the correlation coefficient of the total number of saprophytic bacteria in the semen with the mobility of the thawed semen was only –0.17 (p<0.01) and with the survival of semen only –0.2 (p<0.01). The data obtained have proved for the first time that the examined breeds of the Ukrainian selection have different maximum permissible level of the number of colony forming units of E. coli in the semen. Therefore, not only the coli-titer and the total number of saprophytic bacteria but the absolute number of colony forming units of E.coli bacteria should be determined in the semen of stallions.